The correlation between students' motivation and their speaking achievement - Pramudita, Devi Fitria; Maghfiroh, Ila; Zalhani, Muhammad Rashif; Ratnasari, Nur Qomariyah Dyah; Nafisah, Wardatun; Lestari, Dyah; Umamah, Atik (LPPM Universitas Mercu Buana Yogyakarta, 2023)
This study aims to know the level of motivation in speaking class and to investigate the significant relationship between students’ motivation and speaking achievement. The subject of this study was thirty-four students in the third semester of English Foreign Language (EFL) learners. Twenty-five statements of questionnaires inquiring about motivation levels and speaking achievement were used as the primary data sources. Motivation type was divided into 2, instrumental and integrative motivation, and the data were analyzed using descriptive quantitative. Speaking achievements from the lecturer were divided into excellent, good, average, low, and very low. Pearson Correlation was used to describe the relationship between students’ motivation and achievement. The result showed that students' motivation level was high and had no significant relationship between students’ motivation and their achievement in speaking class, so motivation is not the only factor that can increase students' speaking achievement. This study illustrates that speaking lecturers need to find another factor to boost students' speaking achievement.